Protein Lamtoro leaves (Leucaena leucocephala) with Tannin, Saponin and Oil Protection and the Effect on ruminal undegradable dietary protein (RUDP), and Synthesis of rumen microbial protein - Suhartati, FM (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
A research was conducted to find out the effect of lamtoro (Leucaena leucocephala) leaves with tannin, saponin and oil protection to ruminal undegradable dietary protein (RUDP), and rumen microbial protein. Materials employed in this research were lamtoro leaves (Leucaena leucocephala) which are heated and then processed into mash form: tea leaves (contain 20% of tannin), klerak fruits (contain 48% of saponin) and soybean oil (oil source) as protection agent; and rumen fluid collected from fistulated Peranakan Ongole cows. Experimental in vitro using gas production method (Manke et al., 1979) was employed to assess level of microbial protein. Randomized Block Design was designed to conduct this research, with source of inoculums (rumen fluid) as block. Rumen fluid were collected from fistulated cows in five periods, each block contains of five experimental units. Treatments in this research were protection of lamtoro leaves using different agent, i.e. tannin from tea leaves, saponin from klerak fruits, oil from soybean as much as 2% of dry matter, and unprotected lamtoro leaves as control. Thus, four treatments in this research were as follows: K = control (unprotected lamtoro leaves); TÂ = lamtoro leaves + tannin; S = lamtoro leaves + saponin; and M = lamtoro leaves + oil, so that there were 20 observations. Incubation conducted for 24 hours. Standarized in sacco method by Vanzan et al. (1998) which has been standarizedÂ and modified by Widyobroto et al. (1998) was performed to measure ruminal undegradable dietary protein (RUDP). Each treatment has five replications. 24 hours incubations were conducted in fistulated cows. Completely randomized design was chosen as research design. Variables assessed in this research were synthesis of microbial protein (purin analysis method by Zinn and Owens, 1986) and ruminal undegradable dietary protein (in sacco method). Data analyzed using analysis of varience and honestly significant different (HSD) as further analysis. Research showed that tannin was the best protector agent to obtain highest RUDP and the highest synthesis of microbial protein achieved by lamtoro leaves that protected by saponin. It is suggested that in order to get high RUDP lamtoro leaves should be protected using tannin. (Animal Production 7(1): 52-58 (2005)Â Key Words : Leucaena leucocephala, tannin, saponin, oil, rumen undegradable dietary protein and synthesis of rumen microbial protein